Revisión especial a los procesos de producción y su incidencia en la rentabilidad de la casa deportiva “Fayko Sport” cantón Ventanas periodo 2012 - Pacherre Zapata, Martha Yanine (2015)
This research deals with the particular test production processes and their impact on the profitability of the Sports House "FAYKO SPORT" Canton Windows, 2012. The test period was aimed to evaluate the processes employed and analyze the level of profitability it was obtained; begins with a situational assessment and measurement of internal control, specifically the COSO I methodology, for which an interview was applied to the survey manager and owner operators. In the process of this research field research and literature they were applied to acquire important information, which is then used for planning, execution and reporting emissions. The observation was also used to know preliminarily the control environment in which business activities are developed, and the production department. According to the assessments made regarding internal control components it has a low risk of 23.67% while trust is 76.33% and is considered moderate by what the company needs to improve the organizational structure, responsibility lies with the manager and owner, as there are weaknesses so you must take corrective action. Also the company must optimize resources, in this way may have higher production units that can be sold and thus lead to increased economic returns in 2011 was profitable for 2012 decreased slightly, ie -27% .